Value Addition to forest Produce for Nutrition and Livelihood - Singh, Dheeraj; Chaudhary, M.; Chauhan, P. S.; Prahalad, V. C.; Kavita, A. (Indian Forester, 2009)
Developing countries are being encouraged to diversify their food exports by developing new products and adding more value to existing ones. Adding value to and diversifying food exports depends not only on changing production but also processing systems. The traditional Indian fruits are very rich in nutritional parameters and a variety of by-products can also be prepared from them. This paper describes the importance of some of Indian fruits like Bael, Phalsa, Wood apple and Custard apple. These fruit trees thrive well in stony, infertile and neglected lands and bear heavily without any input. Their bulk use in food industry will improve nutrition and provide variety. With little effort, they can be semi-processed locally for supply to food industry. This can provide employment opportunity to the unskilled but energetic youth. The medicinal values of these fruits have additional attraction and there is a tremendous scope for their further exploration.